Mechanical properties of PP/RPET blends / Wishal Azmy ...[et al.] - Azmy, Wishal; Syahmi, Afiq; Mustafaa, Haikal; Wahid, Mat Uzir; Tan, Suhee
Environment is in critical condition state as many plastic waste such as polyethylene terephthalate (PET) waste are being disposed into landfills. PET is formed by combining two monomers called modified ethylene glycol and purified terephthalic acid and categorize as thermoplastic material which can be recycle;. A study has been conducted on observing the effect on mechanical properties of Polypropylene and Recycle PET blend which was prepared using a single screw extruder and an injection molding. Recycle PET (RPET) with the composition of 5%, 10% and 15% are blend together with PP and their characteristic is investigated through tensile and flexural test. From the results obtained the tensile and flexural strength decreased with the increased of RPET content. Based on previous study, such behaviour is due to the lack of immiscibility and poor interfacial adhesion. This may be overcome by adding a compatibilizer material.